Application of the Improved Multipopulation Genetic Algorithm in the TMD Controlled System considering Soil-Structure Interaction. (9th March 2022) - Nie, Wei; Liu, Shuxian; Yin, Hang; Lu, Shasha; Zhao, Dongxu; Xu, Hong
Abstract : With the advent of globalization, computing speed has increased tremendously, greatly advancing algorithm research in multiple fields. This paper studies the parameter optimization problem of the improved multipopulation genetic algorithm in the tuned mass damper (TMD) structure considering the soil-structure interaction (SSI) effect. The Newmark time-domain analysis method was used to analyze the dynamic response of a 40-story building under the excitation of EL Centro waves and Tangshan waves in China, respectively. The mass, damping coefficient, and spring stiffness of TMD system are used as the design variables of the controller. To reduce structural damage and obtain better comfort, the displacement response and acceleration response are optimized simultaneously in this paper, achieving multiobjective optimization. The results show that the improved multipopulation genetic algorithm method has faster convergence speed and greater accuracy than the traditional genetic algorithm; thus it can be applied to the TMDs parameter optimization of high-rise buildings. Besides, the soil types have a great influence on TMD parameter optimization and structural time history response. If ignoring SSI effect will lead to underestimation of parameter design, the reason is that the soft soil foundations can absorb a lot of seismic energy compared with rigid foundations and then reduce the effect of seismic excitation on the structure. The intention of the research helps researchers to better understand vibration control and provides suggestions for the application of TMD in high-rise buildings.